Depotgestagene zur Kontrazeption bei der Frau: Gemeinsame Stellungnahme der Deutschen Gesellschaft für Gynäkologische Endokrinologie und Fortpflanzungsmedizin (DGGEF) e.V. und des Berufsverbands der Frauenärzte (BVF) e. V. - Rabe, Thomas; Ludwig, M.; Merkle, E.; Ahrendt, H-J.; Bühling, K. J.; Hadji, P.; Mueck, A. O.; Merki, G.; Egarter, C.; König, K.; Albring, C. (Journal für Reproduktionsmedizin und Endokrinologie, 2013)
Drug interactions: There are no data on interactions of injectable progestin-only formulations with other drugs, since no such studies have been performed. The recommendations for interactions of combined oral hormonal contraceptives apply. Applications: Long-term contraception, which for Depo-Clinovir® and Noristerat® is restricted to women who do not tolerate other contraceptives. Sayana® should not be used for young women between 12 and 18 years. Post partum: Non breast-feeding women: DMPA 150 mg: Within the first 5 days post partum; DMPA 104 mg: Within the first 5 days post partum. NET-EN: According to SPC, application is possible immediately after childbirth and miscarriage. Women who are nursing: DMPA 150 mg: Only after a special risk-benefit analysis 6 weeks post partum. DMPA 104 mg: According to SPC, application after 6 weeks post partum. NET-EN: No application in breastfeeding women. Adverse events and their management: Bleeding disorders, body weight, headaches, thrombosis risk (lower than that of ethinylestradiol-containing combination pills), effect on bone with decrease in BMD (only DMPA, not NET-EN), breast cancer (small increase in risk) and practical advice for the first prescription. Relevant national and international publications and weblinks have been compiled. Additional recommendations: Intake of adequate calcium and vitamin D, available through diet or replacement therapy is important for bone health in women of any age. Limited alcohol and nicotine intake is favourable. During long-term use, bone density measurements are recommended. New developments: Combined estrogen/progestogen-containing syringes, new delivery systems, syringes for self-application. J Reproduktionsmed Endokrinol 2013; 10 (1): 18-42.